Predicting Intestinal Adaptation in Pediatric Intestinal Failure: A Retrospective Cohort Study. Issue 5 (May 2019) - Belza, Christina; Fitzgerald, Kevin; de Silva, Nicole; Avitzur, Yaron; Steinberg, Karen; Courtney-Martin, Glenda; Wales, Paul W.
Abstract : Objective: The primary goal in intestinal failure (IF) is adaptation and enteral autonomy (EA). Our goals were to determine the proportion of patients treated for IF by an established intestinal rehabilitation program who achieved EA and to assess the predictors of EA. Background: There have been considerable advancements in the management of IF over the last 15 years, children with short bowel syndrome with a reduction in mortality. Several studies have discussed variables that may influence the ability to attain EA; however, majority were written when mortality rates were considerably higher compared with the current contemporary experience. Methods: A retrospective analysis of infants <12 months with short bowel syndrome referred between 2006 and 2013 (n = 120). Data was collected on IF-related factors and nutritional intake. The cohort was stratified based on achievement of EA. Statistical testing completed using t test, Chi Square, and Cox Proportional Hazards regression ( P < 0.05). Results: EA was achieved in 84 (70.0%) patients. Patients who remained parenteral nutrition dependent were more likely to have volvulus (1.2 vs 22.2%, P < 0.001), shorter percent residual small bowel (29.4 vs 68.6%; P < 0.0001) and colon length (64.6 vs 86.0%; P = 0.001), and no ileocecal valve (61.1 vs 29.8%; P = 0.05). Mortality was also decreased in those who achieved EA (4 vs 22%; P = 0.004). Percent residual small bowel (HR = 1.03; 95% CI 1.02–1.03) and colon (HR = 1.01; 95% CI 1.00–1.02) length were positively associated with EA, while number of septic episodes was negatively associated (HR = 0.95; 95% CI 0.91–0.99). Conclusion: Seventy percent of infants with IF achieved EA. Residual small and large bowel length were the most important predictors of EA and septic events had a negative impact.